Selection for testis size and correlated responses of female reproductive traits in golden hamsters. (17th December 2012) - Furukawa, Tsutomu; Awata, Takashi; Satoh, Masahiro
Abstract Golden hamsters were selected for large (high selection direction: H) and small (low selection direction: L) testis size, as measured in live males at age 13 weeks over six generations. The selection response and correlated responses in female reproductive traits were evaluated in terms of the divergence between H and L lines for testis size. In males, the differences in testis size at 13 weeks, testis weight at 19 weeks, and body weight at 13 and 19 weeks were significant at the 1% level from generation 1 onward. The realized heritability of testis size, as estimated from regression of the selection responses on effective selection differentials, was 0.29. This was similar to the heritability estimated by using the multiple‐trait animal model restricted maximum likelihood (0.30). In females, significant differences in ovulation rate at the 5% level were detected in generations 5 and 6. Litter size 1 day after birth also diverged between the H and L lines, but the difference was not consistently significant. The realized genetic correlation between testis size and ovulation rate was 0.67.